2003
DOI: 10.1108/13595474200300016
|View full text |Cite
|
Sign up to set email alerts
|

‘Please don't let it Happen on my Shift!’ Supporting Staff who are Caring for People with Learning Disabilities who are Dying

Abstract: This paper reports some preliminary lessons from a qualitative study of services that have cared for a person with learning disabilities during a terminal illness. It reflects current concern about access to health care as well as the national priority being placed on improvements in cancer services for all patients.The study documents how the service learned of the person's illness, how they mobilised services and made decisions, how agencies worked together (or not!) and what support staff needed in the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 7 publications
(7 reference statements)
2
36
0
Order By: Relevance
“…Hence, identification of changing needs and adjusting the provision of care as needs change is not always done proactively but rather seems responsive to problems that arise. Moreover, the findings in our study are in accordance with previous research showing that professionals find the end of life a difficult and emotional topic, which could lead to postponing or avoiding conversations about future care (Brown et al 2003;Bekkema et al 2014a;Wiese et al 2014;McKenzie et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, identification of changing needs and adjusting the provision of care as needs change is not always done proactively but rather seems responsive to problems that arise. Moreover, the findings in our study are in accordance with previous research showing that professionals find the end of life a difficult and emotional topic, which could lead to postponing or avoiding conversations about future care (Brown et al 2003;Bekkema et al 2014a;Wiese et al 2014;McKenzie et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the findings in our study are in accordance with previous research showing that professionals find the end of life a difficult and emotional topic, which could lead to postponing or avoiding conversations about future care (Brown et al . ; Bekkema et al . ; Wiese et al .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported on multiple perspectives. Of these, two reported on professionals and relatives 24,25 and one on professionals, relatives, and medical records. 26 No studies focused on the perspective of the patient with ID.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that staff in intellectual disability services are unprepared for the challenges of end‐of‐life care, taken by surprise by its demands, but are willing to overcome these to care for people with intellectual disability at the end of their lives (Brown et al . ; Todd ; Ryan et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…There is some evidence that suggests that the deaths of people with intellectual disability may be challenging for services and that the needs of people with intellectual disability may not be well met at the end of their lives (Bernal & Tuffrey‐Wijne ; Botsford ; Brown et al . ; McCarron et al . ; McLaughlin ; Read & Cartildge, 2012; Read & Thompson‐Hill ; Ryan et al .…”
Section: Introductionmentioning
confidence: 99%